Kalyana Mitta as the fundamental potential for happiness and suffering in Buddhist mindfulness counseling - Venty, Venty (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The dimension of religiosity in counseling activities becomes quite significant because counseling is an activity focused on helping individuals/counselees with all their potential and uniqueness to achieve optimal development. This study aims to examine Buddhist mindfulness counseling. The research method employed in this study was the qualitative method using library research, namely literature search utilizing library sources to obtain research data or limit research activities to Buddhist teachings. This study found a study of the basic philosophy of Buddhist mindfulness counseling, human nature, the function and role of the counselor, the counselee's experience in counseling, the therapeutic relationship between counselor and counselee, counseling techniques, and procedures. Human nature consists of a combination of psychic (nāma) and physical (rūpa) which influence one another. It aims at purification of the mind, overcoming sorrow and anxiety, stopping physical and mental suffering, attaining enlightenment, and attaining liberation of Nibbāna.